Inorganic nitrogen and phosphorus in Western European aerosol and the significance of dry deposition flux into stratified shelf waters. (15th September 2021) - White, Caroline; Ussher, Simon J.; Fitzsimons, Mark F.; Atkinson, Sov; Woodward, E. Malcolm S.; Yang, Mingxi; Bell, Thomas G.
Abstract: Dry deposition of nitrogen (N) and phosphorus (P) from the aerosol phase represents a potential source of nutrients to marine surface waters. To investigate the significance of this deposition pathway, aerosol samples were collected from Penlee Point Atmospheric Observatory in SW England, UK, over a 6-month period (February to July 2015) covering the spring bloom. Samples were analysed for nitrate, ammonium and phosphate and the dry deposition flux of these nutrients calculated to assess its potential impact on primary production in nearby surface seawater. Aerosol-derived N and P deposition fluxes ranged from 2.7 to 620 μmol N m −2 d −1 and 0.16–1.6 μmol P m −2 d −1, respectively. Air mass back trajectory analysis indicated that the highest N fluxes were associated with polluted European air masses, highlighting a significant anthropogenic influence on N-content of aerosols. The N:P ratios of aerosol fluxes and water column concentrations indicated that P deposition was unlikely to be biologically significant in the region. In contrast, aerosol deposition was a significant episodic source of new N to marine phytoplankton after the onset of water column stratification. Carbon fixation estimates indicated that the maximum proportion of new primary production sustained by aerosol-N deposition was 22.4%, a factor of ten higher than the study average. These data suggest that enhanced N-deposition from polluted continental air masses could sustain pulses of surface ocean biological productivity during periods of dissolved N depletion. Highlights: Inorganic aerosol N and P concentrations presented from Penlee Point Atmospheric Observatory (PPAO), Cornwall, UK. Highest N concentrations associated with polluted easterly wind direction from Europe. Dry deposition fluxes of N and P compared to nutrient mixed layer profiles from the Western Channel Observatory, UK. Dry N deposition flux estimated to support as much as 20% of new primary production in the region.